Performance Analysis of Civic Education Lecturers - Cindi yarti simanjuntak; Aseng Padang; Mastiur Verawaty Silalahi; Masni Veronika Situmorang (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the performance of Civic Education lecturers based on student perceptions as a form of learning quality evaluation in higher education. The study uses a quantitative approach with an evaluative survey design, involving 84 active students from the Elementary School Teacher Education and Mechanical Engineering Study Programs at HKBP Nommensen University Pematangsiantar, who were selected purposively. The research instrument was a closed questionnaire with a five-point Likert scale referring to five dimensions of service quality (SERVQUAL), namely teaching readiness, teaching materials, teaching discipline, teaching evaluation, and lecturer personality. The results showed that lecturer performance was generally rated as good to very good, as indicated by the dominance of “Appropriate” and “Very Appropriate” responses across all aspects assessed. These findings indicate that lecturers have carried out the learning process in a planned, consistent manner and in accordance with student needs, so that the results of this study can be used as feedback for lecturers and institutions in their efforts to continuously improve the quality of learning.